Treatment outcomes of MDR-TB and HIV co-infection in Europe. Issue 6 (8th June 2017) - Magis-Escurra, Cecile; Günther, Gunar; Lange, Christoph; Alexandru, Sofia; Altet, Neus; Avsar, Korkut; Bang, Didi; Barbuta, Raisa; Bothamley, Graham; Ciobanu, Ana; Crudu, Valeriu; Davilovits, Manfred; et al.
The ongoing HIV epidemic and the increasing number of patients with drug-resistant tuberculosis (TB) are seriously hampering global TB-control activities, including those in the World Health Organization (WHO) Region Europe. Overall, the prevalence of HIV co-infection in TB patients increased from 3.4% in 2008 to 8% in 2014 in the region [1]. The prevalence of multidrug-resistant (MDR)-TB (drug resistance against at least isoniazid and rifampicin) reported for Europe – 15% in newly diagnosed TB patients and 48% in previously treated TB patients – is the highest in the world [1]. HIV-positive patients with MDR-TB demonstrate a very low proportion of relapse-free cure http://ow.ly/r9sk30bqLBP